2019
DOI: 10.1213/ane.0000000000004028
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Postoperative Residual Neuromuscular Blockade on Hospital Costs and Intensive Care Unit Admission: A Population-Based Cohort Study

Abstract: BACKGROUND: Postoperative residual neuromuscular blockade continues to be a frequent occurrence with a reported incidence rate of up to 64%. However, the effect of postoperative residual neuromuscular blockade on health care utilization remains unclear. We conducted a retrospective cohort study to investigate the effects of postoperative residual neuromuscular blockade on hospital costs (primary outcome), intensive care unit admission rate, and hospital length of stay (secondary outcomes). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 19 publications
0
34
0
2
Order By: Relevance
“…Likewise, although this review evaluates the best available RCT evidence for PPCs, other forms of evidence are available. For example, the adverse influence of neuromuscular blocking drugs is now well established,149150151152153 especially when they are associated with inadequate reversal (a train of four ratio of <0.9). Furthermore, active intraoperative warming, airway suctioning, and choice of airway device are all relevant interventions with an effect on PPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, although this review evaluates the best available RCT evidence for PPCs, other forms of evidence are available. For example, the adverse influence of neuromuscular blocking drugs is now well established,149150151152153 especially when they are associated with inadequate reversal (a train of four ratio of <0.9). Furthermore, active intraoperative warming, airway suctioning, and choice of airway device are all relevant interventions with an effect on PPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, NMBA reversal with neostigmine and anticholinesterases might be associated with increased risk of cardiovascular complications in the high-risk group (age > 70 years, undergoing vascular surgery, prior history of atrial fibrillation) [29,35]. Furthermore, a recent cohort study reported that PORC in the post-anesthesia care unit is associated with higher rates of ICU admission [36]. Therefore, the results of our current study suggested that efforts to minimize PORC using sugammadex could result in improvement of fatal outcomes, such as 90-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,13,17 Recent data suggest that reversal of neuromuscular block with neostigmine and an anticholinesterase may be associated with increased risk of cardiovascular complications in selected populations, such as patients >70 yr old, undergoing vascular surgery, or with prior history of atrial fibrillation. 18 These complications could in part explain why patients with residual neuromuscular block demonstrate an increase in ICU admission rate and prolonged hospital length of stay, 19 and increased rates of readmission among ambulatory patients. 7 The findings of Oh and colleagues 4 are interesting and thought provoking in this context.…”
Section: Methodological Issues In Observational Studies Of Readmissiomentioning
confidence: 99%